Health Effects of Typhoon Sendong in Iligan City An Exploratory Study - Cabartija, Davie Ross C. (Langkit : the Official journal of the College of Arts & Social Sciences Mindanao State University-Iligan Institute of Technology, 2013)
This study determined the immediate and intermediate health effects of Typhoon Sendong as experienced in Iligan City. The Disaster Risk Reduction Management and Climate Change Adaptation (DRR-CAA) Framework provided the theoretical premise of this study which involved reviewing the Emergency Room records of Gregorio T. Lluch Memorial Hospital. A quantitative retrospective study employing descriptive statistics was used in the data analysis.